2012
DOI: 10.1371/journal.pone.0038438
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals of FGF19 & FGF21 Action In Vitro and In Vivo

Abstract: Fibroblast growth factors 19 (FGF19) and 21 (FGF21) have emerged as key regulators of energy metabolism. Several studies have been conducted to understand the mechanism of FGF19 and FGF21 action, however, the data presented has often been inconsistent and at times contradictory. Here in a single study we compare the mechanisms mediating FGF19/FGF21 actions, and how similarities/differences in actions at the cellular level between these two factors translate to common/divergent physiological outputs. Firstly, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
104
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(114 citation statements)
references
References 41 publications
(85 reference statements)
10
104
0
Order By: Relevance
“…Injection of recombinant FGF21 normalizes blood glucose levels, improves insulin sensitivity, and corrects dyslipidemia in several rodent and nonrodent animal models of type 2 diabetes (12,16,17). It is highly expressed in the liver and whole-pancreas extracts, with lower expression levels in muscle and adipose tissue (18,19). Given the pleiotropic actions of FGF21 on whole-body glucose regulation, we hypothesized that FGF21 may be a factor contributing to glucose regulation in insulin-deficient Gcgr 2/2 mice.…”
Section: /2mentioning
confidence: 99%
“…Injection of recombinant FGF21 normalizes blood glucose levels, improves insulin sensitivity, and corrects dyslipidemia in several rodent and nonrodent animal models of type 2 diabetes (12,16,17). It is highly expressed in the liver and whole-pancreas extracts, with lower expression levels in muscle and adipose tissue (18,19). Given the pleiotropic actions of FGF21 on whole-body glucose regulation, we hypothesized that FGF21 may be a factor contributing to glucose regulation in insulin-deficient Gcgr 2/2 mice.…”
Section: /2mentioning
confidence: 99%
“…epigenetics; gene silencing; MIST1; pancreatitis; histone methylation FIBROBLAST GROWTH FACTOR 21 (FGF21) is an important regulator of metabolism, belonging to the endocrine family of FGFs, which includes FGF15/19 and FGF23 (1,24). FGF21 increases insulin production and glucose uptake (52), promotes ketogenesis (2,18), and enhances conversion of white to brown adipose tissue (14).…”
mentioning
confidence: 99%
“…FGF21 activity requires nearly intact amino and carboxyl termini in order to facilitate N-terminal receptor and C-terminal KLB binding [13,14]. In one study, KLB knockout mice were shown to have stunted metabolic effects when injected with FGF21, revealing its activity dependence on KLB [15].…”
mentioning
confidence: 99%
“…In one study, KLB knockout mice were shown to have stunted metabolic effects when injected with FGF21, revealing its activity dependence on KLB [15]. Additionally, deletions of N-terminal residues interfere with the FGF receptor (FGFR) activation even though KLB interaction to the C-terminal end remains uninterrupted [5,13], thus placing FGFR binding at the extreme N-terminus. In obese mice, an N-terminal truncated variant of FGF21 was administered in competition with the wild-type form.…”
mentioning
confidence: 99%